Human apolipoprotein A-II reduces atherosclerosis in knock-in rabbits. (January 2021) - Koike, Tomonari; Koike, Yui; Yang, Dongshan; Guo, Yanhong; Rom, Oren; Song, Jun; Xu, Jie; Chen, Yajie; Wang, Yanli; Zhu, Tianqing; Garcia-Barrio, Minerva T.; Fan, Jianglin; et al.
Abstract: Background and aims: Apolipoprotein A-II (apoAII) is the second major apolipoprotein of the high-density lipoprotein (HDL) particle, after apoAI. Unlike apoAI, the biological and physiological functions of apoAII are unclear. We aimed to gain insight into the specific roles of apoAII in lipoprotein metabolism and atherosclerosis using a novel rabbit model. Methods: Wild-type (WT) rabbits are naturally deficient in apoAII, thus their HDL contains only apoAI. Using TALEN technology, we replaced the endogenous apoAI in rabbits through knock-in (KI) of human apoAII. The newly generated apoAII KI rabbits were used to study the specific function of apoAII, independent of apoAI. Results: ApoAII KI rabbits expressed exclusively apoAII without apoAI, as confirmed by RT-PCR and Western blotting. On a standard diet, the KI rabbits exhibited lower plasma triglycerides (TG, 52%, p < 0.01) due to accelerated clearance of TG-rich particles and higher lipoprotein lipase activity than the WT littermates. ApoAII KI rabbits also had higher plasma HDL-C (28%, p < 0.05) and their HDL was rich in apoE, apoAIV, and apoAV. When fed a cholesterol-rich diet for 16 weeks, apoAII KI rabbits were resistant to diet-induced hypertriglyceridemia and developed significantly less aortic atherosclerosis compared to WT rabbits. HDL isolated from rabbits with apoAII KI had similar cholesterol efflux capacity and anti-inflammatory effects as HDL isolated from the WT rabbits. Conclusions: ApoAII KI rabbits developed less atherosclerosis than WT rabbits, possibly through increased plasma HDL-C, reduced TG and atherogenic lipoproteins. These results suggest that apoAII may serve as a potential target for the treatment of atherosclerosis. Graphical abstract: Image 1 Highlights: We generated a human apoAII knock-in (KI) rabbit, in which human a poAII replaced the endogenous rabbit a poAI gene. On a standard diet, apoAII KI rabbits exhibited lower TG-rich lipoproteins and higher lipoprotein lipase activity than WT. ApoAII KI rabbits had higher HDL-C levels and HDL particles rich in apoE, apoAIV, and apoAV protein. On a cholesterol-rich diet, apoAII KI rabbits developed significantly less aortic atherosclerosis. These results underscore a better function of apoAII HDL compared with apoAI, suggesting a potential for targeted therapies.